2016
DOI: 10.1097/jpn.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Health-Related Quality of Life in Pregnancy

Abstract: The aim of this study was to investigate sleep quality and health-related quality of life in pregnancy. In a cross-sectional design, 492 women (292 pregnant and 200 nonpregnant healthy controls) were included in this study between November 2014 and June 2015. Participants completed a survey on sociodemographic characteristics, the Pittsburgh Sleep Quality Index (PSQI), and the European Quality of Life-5 Dimensions (EQ-5D). The PSQI total and EQ-5D scores of pregnant women were significantly worse than the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 43 publications
8
39
3
3
Order By: Relevance
“…Education but not working status was associated in previous findings with health-related quality of life during pregnancy [16]. Our results were consistent with these findings since education was positively correlated to psychological health, social relationships and environment domains, while occupational category was not associated with any domain of the WHOQOL-brief.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Education but not working status was associated in previous findings with health-related quality of life during pregnancy [16]. Our results were consistent with these findings since education was positively correlated to psychological health, social relationships and environment domains, while occupational category was not associated with any domain of the WHOQOL-brief.…”
Section: Resultssupporting
confidence: 92%
“…Psychiatric disorders can affect the psychological as well as the physical domains of the QOL during pregnancy [16]. This was also observed in our study since increased worry was associated with a decrease in two domains of QOL: environment and psychological while depression was associated with a decrease in all QOL domains.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Poorer global sleep quality, subjective sleep quality, lower sleep efficiency and sleep disturbances were most prevalent during third trimester. These findings were supported by several studies [9,10], including a report of Chinese pregnant women population [33]. The sleep patterns of most pregnant women changed during pregnancy, which might be the reason [6].…”
Section: Discussionsupporting
confidence: 73%
“…As pregnancy proceeds, both the number and duration of sleep disorders increase [6]. Sut et al [9] and Facco et al [10] indicated that the risk of poor sleep quality increased in the second and third trimester when compared with the first trimester. Depression symptom was previously indicated to be associated with sleep disturbances during pregnancy [11].…”
Section: Introductionmentioning
confidence: 99%